Full-Construct Biomechanical Evaluation of Femoral Cortical Suspensory Fixation for Anterior Cruciate Ligament Reconstruction in a Porcine Knee Model - Tomas F. Vega; Juan Bernardo Villarreal Espinosa; Elizabeth Shewman; Zeeshan A. Khan; Harsh Singh; Brady T. Williams; Thomas Alter; Ron Gilat; Safa Gursoy; Andrew S. Bi; Jorge Chahla (Orthopaedic Journal of Sports Medicine, 2026)
Background: Although recent studies show no clinical outcome differences between cortical button suspensory fixation devices for anterior cruciate ligament reconstruction (ACLR), biomechanical mechanisms of elongation and failure remain unclear for adjustable-loop devices (ALDs) and fixed-loop devices (FLDs). Purpose: To compare biomechanical outcomes of ALDs with button-locking device (BLD), suture-locking device (SLD), and dual-locking device (DLD) mechanisms relative to an industry-standard FLD. Study Design: Controlled laboratory study. Methods: Five femoral cortical suspension devices (n = 11 each; total = 55 constructs) were tested using porcine femurs and bovine tendons simulating doubled hamstring grafts: EndoButton (FLD), Infinity Button (BLD), ProCinch (SLD1), UltraButton (SLD2), and TightRope (DLD). Constructs underwent cyclic loading simulating early (10-250 N, 500 cycles) and late (10-400 N, 500 cycles) rehabilitation, followed by pull-to-failure at 50 mm/min. Outcomes included excursion over simulated early and late rehabilitation and the cumulative total of both loading protocols. Also assessed were maximum load, stiffness, energy to failure, and failure mode, categorized as bone, button, suture loop rupture, tendon, or locking mechanism failure. Results: No significant differences were observed in cyclic loading at 500 cycles of 10 to 250 N or across the cumulative 1000 loading cycles between any ALD and the FLD. During cyclic loading at 10 to 400 N specifically, the BLD (3.34 ± 1.71 mm) and DLD (3.63 ± 1.18 mm) demonstrated greater excursion than the FLD (1.49 ± 0.36 mm; both P < .01). SLD1 (1270.5 ± 204.7 N) and SLD2 (1232.7 ± 185.2 N) withstood higher maximum loads than the BLD (1011.4 ± 95.8 N) and DLD (1018.4 ± 63.1 N; P < .05), although no differences were observed between the FLD and all ALDs combined. Stiffness did not differ across groups. BLD and DLD constructs most often failed by suture rupture, whereas the FLD and SLDs failed by button failure. Suture rupture was associated with greater excursion during cyclic loading at 10 to 400 N, lower maximum load, and reduced energy absorption compared with button failure ( P < .05). Conclusion: All constructs exceeded forces expected during early and total rehabilitation after ACLR, confirming adequate initial biomechanical strength across ALDs and FLDs. Differences in excursion and load to failure were associated with locking mechanism design and resultant failure mode, although clinical implications remain uncertain. Clinical Relevance: Although mechanical behavior varied by device mechanism, all systems provided fixation above physiologic loads, supporting that design-specific differences influence how devices fail but not their ability to provide adequate early postoperative stability in ACLR.